What Determines the Capital Share over the Long Run of History? - Erik Bengtsson; Enrico Rubolino; Daniel Waldenström (Institute of Labor Economics (IZA), 2020)
This paper analyzes the determinants of the labor-capital split in national income for 20 countries since the late 1800s. Our main identification strategy focuses on unique historical quasi-experimental events: i) the introduction of universal suffrage, ii) close election wins of left-wing governments, iii) decolonization, iv) unionization shocks, and v) wars. We also run instrumented panel regressions. Our findings show that the capital share decreased in response to radical institutional and political shifts, such as the introduction of universal suffrage in the early 1900s, the undoing of colonialism and the implementation of redistributive policies during the post-war period. By contrast, the capital share increased following the erosion of trade unionism since the 1980s. Wars, despite destroying the capital stock, generated windfall profits that increased the capital share.
Keywords: D33; E02; N00; 330; inequality; factor shares; event study; economic history; institutions